Climate Evolution Through the Onset and Intensification of Northern Hemisphere Glaciation - Karas, C (John Wiley and Sons Inc, 2023)
The Pliocene Epoch (∼5.3–2.6 million years ago, Ma) was characterized by a warmer than present climate with smaller Northern Hemisphere ice sheets, and offers an example of a climate system in long-term equilibrium with current or predicted near-future atmospheric CO2 concentrations (pCO2). A long-term trend of ice-sheet expansion led to more pronounced glacial (cold) stages by the end of the Pliocene (∼2.6 Ma), known as the “intensification of Northern Hemisphere Glaciation” (iNHG). We assessed the spatial and temporal variability of ocean temperatures and ice-volume indicators through the late Pliocene and early Pleistocene (from 3.3 to 2.4 Ma) to determine the character of this climate transition. We identified asynchronous shifts in long-term means and the pacing and amplitude of shorter-term climate variability, between regions and between climate proxies. Early changes in Antarctic glaciation and Southern Hemisphere ocean properties occurred even during the mid-Piacenzian warm period (∼3.264–3.025 Ma) which has been used as an analog for future warming. Increased climate variability subsequently developed alongside signatures of larger Northern Hemisphere ice sheets (iNHG). Yet, some regions of the ocean felt no impact of iNHG, particularly in lower latitudes. Our analysis has demonstrated the complex, non-uniform and globally asynchronous nature of climate changes associated with the iNHG. Shifting ocean gateways and ocean circulation changes may have pre-conditioned the later evolution of ice sheets with falling atmospheric pCO2. Further development of high-resolution, multi-proxy reconstructions of climate is required so that the full potential of the rich and detailed geological records can be realized. © 2023. The Authors.